Polyamide resin composition for welding and engine cooling water system part made of the same
A polyamide resin composition with specific fibrous and amorphous resin ratios addresses the challenge of high-pressure welding in engine cooling water system parts, ensuring high welding strength and productivity with enhanced heat resistance and low water absorption.
Patent Information
- Application Number
- JP2020210516
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-18
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2040-12-18
AI Technical Summary
Existing polyamide resin compositions for engine cooling water system parts in automobiles face challenges in achieving high welding strength when welded with high pressure, leading to longer welding times and reduced productivity.
A polyamide resin composition comprising 0 to 150 parts by mass of fibrous reinforcing material and 5 to 50 parts by mass of amorphous resin per 100 parts by mass of semi-aromatic polyamide resin, with specific molecular weight and composition ratios, enhancing welding strength and productivity.
The composition maintains high welding strength even with high pressure, allowing for shorter welding times and improved productivity, while also offering high heat resistance and low water absorption, suitable for engine cooling water system parts.
Smart Images

Figure 0007619036000001 
Figure 0007619036000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a reinforced polyamide resin composition suitable for molding molded parts having welded parts, such as engine cooling water system parts for automobiles. More specifically, the present invention relates to a polyamide resin composition for engine cooling water system parts, which has excellent calcium chloride resistance, antifreeze resistance, low water absorption, etc. and is suitable for applications in which the parts are used in contact with cooling water in an engine room, such as radiator tank parts, water pump parts, sub-tanks, thermostat housings, etc. [Background technology]
[0002] With the weight reduction of automobiles, the replacement of metals with resin materials is being promoted. Automobile parts, especially resin parts used in the engine room, are used in a harsh environment due to the increase in engine coolant temperature and the increase in temperature in the engine room associated with the high performance and high power of the engine. Antifreeze liquid (LLC) is used to cool engines used in harsh thermal environments. Therefore, resin materials are required to be resistant to antifreeze liquid (Patent Document 1). In addition, with the progress of molding processing technology for resin materials (blow molding, extrusion molding), it has become possible to adapt to complex part shapes in the engine room. However, in product design, there are still cases where the mechanical strength including weld strength does not reach the target with the above-mentioned construction method alone, or parts must be designed separately due to complex shapes. When parts are separated, a process of welding parts made of resin material together to complete the product is generally known. Therefore, resin materials are required to have properties that can handle the welding process.
[0003] There has been research into the welding of polyamide 6 and polyamide 66, and the parameters of the welding conditions include pressure, amplitude, welding time, and frequency (Non-Patent Document 1). In addition, with regard to the welding conditions and welding strength, it has been proposed that the higher the pressure, the lower the welding strength (Non-Patent Document 2). However, the disadvantage of lowering the pressure is that the welding time becomes longer in order to obtain sufficient welding strength. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2012-153798 A [Non-patent literature]
[0005] [Non-Patent Document 1] POLYMER ENGINEERING AND SCIENCE, APRIL 2004, Vol. No.4, p.760~771 [Non-Patent Document 2] Journal of THERMOPLASTIC COMPOSUTE MATERIALS Vol.16 March 2003, p.101~119 Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention aims to provide a polyamide resin composition that is capable of exhibiting high weld strength even when welded with a high pressure in order to shorten the welding time and increase productivity. [Means for solving the problem]
[0007] In order to achieve the above object, the present inventors have intensively studied the composition of polyamides and have completed the present invention.
[0008] That is, the present invention has the following configurations (1) to (6). (1) A polyamide resin composition for welding, comprising 100 parts by mass of a semi-aromatic polyamide resin (A), 0 to 150 parts by mass of a fibrous reinforcing material (B), and 5 to 50 parts by mass of a non-crystalline resin (C). (2) The polyamide resin composition for welding according to (1), wherein the semi-aromatic polyamide resin (A) is a copolymer polyamide resin having as its constituent components (a) 50 to 80 mol % of hexamethylene terephthalamide units and (b) 50 to 20 mol % of undecane amide units. (3) The polyamide resin composition for welding according to (1) or (2), wherein the semi-aromatic polyamide resin (A) has a weight average molecular weight of 15,000 to 60,000. (4) The polyamide resin composition for welding according to any one of (1) to (3), wherein the non-crystalline resin (C) is a non-crystalline polyamide resin. (5) A molded part having a welded portion made of the polyamide resin composition according to any one of (1) to (4). (6) An engine cooling water system part made of the polyamide resin composition according to any one of (1) to (4). Effect of the Invention
[0009] The polyamide resin composition of the present invention maintains a weld strength equal to or greater than that achieved by low pressure welding even when welded with high pressure, and can be welded in a short time, which makes it excellent in productivity and optimal for molded parts having welded parts.Furthermore, it has high heat resistance and low water absorption, making it suitable for engine cooling water system parts. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The polyamide resin composition of the present invention is intended to be used for molded parts having welded parts, particularly engine cooling water system parts, such as radiator tank parts, coolant reserve tanks, water pipes, water inlet pipes, water outlet pipes, water pump housings, water pump impellers, water valves, and coolant sub-tank parts.
[0011] The polyamide resin composition for welding of the present invention is an optimal polyamide resin composition for obtaining a desired welded molded part by vibration welding molded articles made of the polyamide resin composition together.
[0012] The polyamide resin composition of the present invention contains 100 parts by mass of a semi-aromatic polyamide resin (A), 0 to 150 parts by mass of a fibrous reinforcing material (B), and 5 to 50 parts by mass of a non-crystalline resin (C).
[0013] The semi-aromatic polyamide resin (A) is a polyamide resin whose polyamide components are a diamine component and a dicarboxylic acid component, or a polyamide resin whose polyamide components are a diamine component, a dicarboxylic acid component and an aminocarboxylic acid (or lactam) component, and any one of the diamine component, the dicarboxylic acid component and the aminocarboxylic acid (or lactam) component is an aromatic component. The semi-aromatic polyamide resin (A) is preferably a crystalline polyamide resin, and its melting point is preferably 280 to 330°C.
[0014] The semi-aromatic polyamide resin (A) is preferably a copolymer polyamide resin comprising (a) 50 to 80 mol % of hexamethylene terephthalamide units and (b) 50 to 20 mol % of undecane amide units.
[0015] The semi-aromatic polyamide resin (A) is blended to realize excellent moldability in addition to high heat resistance, fluidity, and low water absorption, and contains a specific ratio of a component (a) corresponding to polyamide 6T and a component (b) corresponding to polyamide 11. Not only does it greatly improve on the high water absorption that is a drawback of conventional 6T nylon (e.g., polyamide 6T6I consisting of terephthalic acid / isophthalic acid / hexamethylenediamine, polyamide 6T66 consisting of terephthalic acid / adipic acid / hexamethylenediamine, polyamide 6T6I66 consisting of terephthalic acid / isophthalic acid / adipic acid / hexamethylenediamine, polyamide 6T / M-5T consisting of terephthalic acid / hexamethylenediamine / 2-methyl-1,5-pentamethylenediamine, and polyamide 6T6 consisting of terephthalic acid / hexamethylenediamine / ε-caprolactam), it also has the characteristic of excellent durability of the reinforcing effect due to the fibrous reinforcing material. Furthermore, since it has a flexible long-chain aliphatic skeleton derived from the polyamide 11 component, it also has the characteristic of easily ensuring fluidity.
[0016] Component (a) corresponds to 6T nylon obtained by polycondensation of equimolar amounts of hexamethylenediamine (6) and terephthalic acid (T).
[0017] Component (a) is the main component of semi-aromatic polyamide resin (A) and plays a role in imparting excellent heat resistance, mechanical properties, sliding properties, etc. to semi-aromatic polyamide resin (A). The blending ratio of component (a) in semi-aromatic polyamide (A) is preferably 50 to 80 mol%, more preferably 55 to 75 mol%, further preferably 60 to 70 mol%, and particularly preferably 62 to 68 mol%. If the blending ratio of component (a) is less than the above lower limit, crystallization of the crystalline component 6T nylon may be inhibited by the copolymerization component, which may lead to a decrease in moldability and high-temperature properties, while if it exceeds the above upper limit, the melting point may become too high and decompose during processing.
[0018] Component (b) corresponds to nylon 11 obtained by polycondensation of 11-aminoundecanoic acid or undecane lactam.
[0019] The (b) component is intended to improve the water absorption and fluidity, which are defects of the (a) component, and has the role of adjusting the melting point and heating crystallization temperature of the semi-aromatic polyamide resin (A) to improve moldability, the role of reducing the water absorption rate to improve problems caused by changes in physical properties and dimensions when absorbing water, and the role of improving fluidity when melted by introducing a flexible skeleton. The blending ratio of the (b) component in the semi-aromatic polyamide resin (A) is preferably 50 to 20 mol%, more preferably 45 to 25 mol%, even more preferably 40 to 30 mol%, and particularly preferably 38 to 32 mol%. If the blending ratio of the (b) component is less than the above lower limit, the melting point of the semi-aromatic polyamide resin (A) may not be sufficiently lowered, which may result in insufficient moldability, and the effect of reducing the water absorption rate of the obtained resin may be insufficient, which may lead to instability of physical properties such as a decrease in mechanical properties when absorbing water. If the above upper limit is exceeded, the melting point of the semi-aromatic polyamide resin (A) will be too low, causing the crystallization rate to slow down, and moldability may actually be deteriorated. In addition, the amount of component (a) corresponding to 6T nylon will be so small that mechanical properties and heat resistance may be insufficient.
[0020] In addition to the above components (a) and (b), the semi-aromatic polyamide resin (A) may be copolymerized with up to 20 mol% of (c) a constituent unit obtained from an equimolar salt of a diamine and a dicarboxylic acid other than the constituent unit (a) above, or a constituent unit obtained from an aminocarboxylic acid or lactam other than the constituent unit (b) above. Component (c) has the role of imparting other properties to the semi-aromatic polyamide resin (A) that cannot be obtained with nylon 6T or nylon 11, or of further improving the properties obtained with nylon 6T or nylon 11, and specific examples of the copolymerization components include the following: The diamine components include 1,2-ethylenediamine, 1,3-trimethylenediamine, 1,4-tetramethylenediamine, 1,5-pentamethylenediamine, 2-methyl-1,5-pentamethylenediamine, 1,6-hexamethylenediamine, 1,7-heptamethylenediamine, 1,8-octamethylenediamine, 1,9-nonamethylenediamine, 2-methyl-1,8-octamethylenediamine, 1,10-decamethylenediamine, 1,11-undecamethylenediamine, 1,12-dodecamethylenediamine, and 1,13-tridecamethylenediamine. Examples of the diamine include aliphatic diamines such as 1,16-hexadecamethylenediamine, 1,18-octadecamethylenediamine, and 2,2,4 (or 2,4,4)-trimethylhexamethylenediamine, alicyclic diamines such as piperazine, cyclohexanediamine, bis(3-methyl-4-aminohexyl)methane, bis-(4,4'-aminocyclohexyl)methane, and isophoronediamine, and aromatic diamines such as metaxylylenediamine, paraxylylenediamine, paraphenylene diamine, and metaphenylene diamine, and hydrogenated products thereof. As the dicarboxylic acid component, the following dicarboxylic acids or acid anhydrides can be used.Examples of dicarboxylic acids include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, orthophthalic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 4,4'-diphenyldicarboxylic acid, 2,2'-diphenyldicarboxylic acid, 4,4'-diphenyletherdicarboxylic acid, 5-sodium sulfonate isophthalic acid, and 5-hydroxyisophthalic acid; and aliphatic or alicyclic dicarboxylic acids such as fumaric acid, maleic acid, succinic acid, itaconic acid, adipic acid, azelaic acid, sebacic acid, 1,11-undecanedioic acid, 1,12-dodecanedioic acid, 1,14-tetradecanedioic acid, 1,18-octadecanedioic acid, 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, 4-methyl-1,2-cyclohexanedicarboxylic acid, and dimer acid. Other examples include lactams such as ε-caprolactam and 12-lauryllactam, and aminocarboxylic acids which are ring-opened structures of these.
[0021] Examples of catalysts used in producing the semi-aromatic polyamide resin (A) include phosphoric acid, phosphorous acid, hypophosphorous acid, or their metal salts, ammonium salts, and esters. Specific examples of metal species of metal salts include potassium, sodium, magnesium, vanadium, calcium, zinc, cobalt, manganese, tin, tungsten, germanium, titanium, and antimony. Examples of esters include ethyl ester, isopropyl ester, butyl ester, hexyl ester, isodecyl ester, octadecyl ester, decyl ester, stearyl ester, and phenyl ester. In addition, from the viewpoint of improving melt retention stability, it is preferable to add an alkali compound such as sodium hydroxide, potassium hydroxide, or magnesium hydroxide.
[0022] The semi-aromatic polyamide resin (A) preferably has a weight average molecular weight of 15,000 to 60,000. The larger the molecular weight, the more the starting points for entanglement of polymer chains, and the higher the mechanical strength and strength during welding. The weight average molecular weight is more preferably 18,000 to 40,000, and further preferably 23,000 to 33,000.
[0023] The relative viscosity (RV) of the semi-aromatic polyamide resin (A) measured in 96% by mass concentrated sulfuric acid at 20° C. is preferably 0.4 to 4.0, more preferably 1.0 to 3.0, and further preferably 1.5 to 2.5. Methods for adjusting the relative viscosity of the polyamide within a certain range include a method for adjusting the molecular weight.
[0024] The amount of terminal groups and the molecular weight of the semi-aromatic polyamide resin (A) can be adjusted by a method of polycondensation by adjusting the molar ratio of the amount of amino groups to the amount of carboxyl groups or a method of adding a terminal blocking agent.
[0025] The end-capping agent may be used when the raw materials are charged, at the start of polymerization, in the later stage of polymerization, or at the end of polymerization. The end-capping agent is not particularly limited as long as it is a monofunctional compound that is reactive with the amino group or carboxyl group at the polyamide end, and examples of the end-capping agent that can be used include monocarboxylic acids or monoamines, acid anhydrides such as phthalic anhydride, monoisocyanates, monoacid halides, monoesters, and monoalcohols. Examples of the end-capping agent include aliphatic monocarboxylic acids such as acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecanoic acid, myristic acid, palmitic acid, stearic acid, pivalic acid, and isobutyric acid; alicyclic monocarboxylic acids such as cyclohexylcarboxylic acid; aromatic monocarboxylic acids such as benzoic acid, toluic acid, α-naphthalenecarboxylic acid, β-naphthalenecarboxylic acid, methylnaphthalenecarboxylic acid, and phenylacetic acid; acid anhydrides such as maleic anhydride, phthalic anhydride, and hexahydrophthalic anhydride; aliphatic monoamines such as methylamine, ethylamine, propylamine, butylamine, hexylamine, octylamine, decylamine, stearylamine, dimethylamine, diethylamine, dipropylamine, and dibutylamine; alicyclic monoamines such as cyclohexylamine and dicyclohexylamine; and aromatic monoamines such as aniline, toluidine, diphenylamine, and naphthylamine.
[0026] The semi-aromatic polyamide resin (A) can be produced by a conventional method, but can be easily synthesized, for example, by polycondensation reaction of hexamethylenediamine and terephthalic acid, which are raw material monomers of component (a), and 11-aminoundecanoic acid or undecane lactam, which are raw material monomers of component (b), and other raw material monomers of component (c) as necessary. The order of polycondensation reaction is not particularly limited, and all raw material monomers may be reacted at once, or some raw material monomers may be reacted first, followed by the remaining raw material monomers. The polymerization method is not particularly limited, and may be a continuous process from raw material charging to polymer production, or a method in which an oligomer is once produced and then polymerized in a separate process using an extruder or the like, or the oligomer is polymerized by solid-phase polymerization. The ratio of each structural unit in the synthesized copolymerized polyamide can be controlled by adjusting the charging ratio of the raw material monomers.
[0027] Examples of the fibrous reinforcing material (B) include glass fibers, carbon fibers, boron fibers, ceramic fibers, and metal fibers, and other needle-shaped reinforcing materials such as potassium titanate whiskers, aluminum borate whiskers, zinc oxide whiskers, calcium carbonate whiskers, magnesium sulfate whiskers, and wollastonite. As the fibrous reinforcing material (B), glass fibers are preferred. As the glass fibers, chopped strands or continuous filament fibers having a length of 0.1 mm to 100 mm can be used. As the cross-sectional shape of the glass fibers, glass fibers having circular and noncircular cross sections can be used. The diameter of the circular cross-section glass fibers is 20 μm or less, preferably 15 μm or less, and more preferably 10 μm or less. In addition, glass fibers having noncircular cross sections are preferred from the viewpoint of physical properties and fluidity. Glass fibers having noncircular cross sections include those having a substantially elliptical, substantially oval, or substantially cocoon-shaped cross section perpendicular to the longitudinal direction of the fiber length, and the flatness is preferably 1.5 to 8. Here, the flatness is the ratio of the long diameter to the short diameter when the long side of the rectangle with the smallest area circumscribing the cross section perpendicular to the longitudinal direction of the glass fiber is taken as the long diameter and the short side of the rectangle is taken as the short diameter. The thickness of the glass fiber is not particularly limited, but the short diameter is about 1 to 20 μm and the long diameter is about 2 to 100 μm. In addition, the glass fiber is preferably cut into a fiber bundle into chopped strands with a fiber length of about 1 to 20 mm. Furthermore, in order to increase the surface reflectance of the polyamide resin composition, it is preferable to use one with a high refractive index by changing the glass composition or surface treatment, since it is preferable that the refractive index difference from the semi-aromatic polyamide resin (A) is large.
[0028] The proportion of the fibrous reinforcing material (B) is 0 to 150 parts by mass relative to 100 parts by mass of the semi-aromatic polyamide resin (A). If the proportion of the fibrous reinforcing material (B) exceeds the upper limit, the mechanical strength of the molded product is improved, but the welding strength is significantly reduced. If the polyamide resin composition does not require mechanical strength, it may not contain the fibrous reinforcing material (B). When the fibrous reinforcing material (B) is contained, the proportion of the fibrous reinforcing material (B) is preferably 30 to 100 parts by mass, more preferably 50 to 80 parts by mass, relative to 100 parts by mass of the semi-aromatic polyamide resin (A).
[0029] Examples of the amorphous resin (C) include PMMA (polymethyl acrylate) resin, PS (polystyrene) resin, PC (polycarbonate) resin, ABS (acrylonitrile butadiene styrene) resin, PEI (polyetherimide) resin, PAI (polyamideimide) resin, amorphous maleimide resin, and amorphous polyamide resin. From the viewpoint of compatibility with the semi-aromatic polyamide resin (A), the amorphous resin (C) is preferably an amorphous polyamide resin. Preferred examples of the amorphous polyamide resin include polyamide 6T6I, polyamide PACM14 (polybis(3-methyl-4-aminohexyl)methanetetradecamide), polyamide PACM12 (polybis(3-methyl-4-aminohexyl)methaneisophthalamide), and the like, with polyamide 6T6I, which is the same semi-aromatic polyamide resin as the semi-aromatic polyamide resin (A), being particularly preferred. Compatibility in this case refers to the ability to undergo an amide exchange reaction with the semi-aromatic polyamide resin (A).
[0030] The ratio of the amorphous resin (C) is 5 to 50 parts by mass relative to 100 parts by mass of the semi-aromatic polyamide resin (A). With the amorphous resin (C) in this range, high welding strength can be achieved even when welding is performed with a high pressure. The ratio of the amorphous resin (C) is preferably 15 to 50 parts by mass relative to 100 parts by mass of the semi-aromatic polyamide resin (A).
[0031] The reason for the improvement of the welding strength by adding the amorphous resin (C) to the semi-aromatic polyamide resin (A) is considered to be as follows. During the vibration welding process of the molded products made of the polyamide resin composition, the polymer chains of the semi-aromatic polyamide resin (A) are oriented in the vibration direction, and the welded part between the molded products solidifies with the polymer chains disentangled, which is considered to reduce the welding strength. By adding the amorphous resin (C) to the semi-aromatic polyamide resin (A), the crystallization temperature of the polyamide resin composition can be lowered to delay the time until solidification, and as a result, it is considered that the entanglement of the polymer chains at the welded part between the molded products increases by trying to return to a non-oriented state, leading to an improvement in strength. This effect is more pronounced when the amorphous resin (C) is an amorphous polyamide resin, particularly when the amorphous resin (C) is an amorphous semi-aromatic polyamide resin.
[0032] The polyamide resin composition of the present invention may contain a non-fibrous or non-acicular filler as necessary. Examples of non-fibrous or non-acicular fillers include reinforcing fillers, conductive fillers, magnetic fillers, flame-retardant fillers, heat-conductive fillers, and fillers for suppressing thermal yellowing, depending on the purpose. Specific examples include glass beads, glass flakes, glass balloons, silica, talc, kaolin, mica, alumina, hydrotalcite, montmorillonite, graphite, carbon nanotubes, fullerenes, indium oxide, tin oxide, iron oxide, magnesium oxide, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, red phosphorus, calcium carbonate, lead zirconate titanate, barium titanate, aluminum nitride, boron nitride, zinc borate, barium sulfate, and non-acicular wollastonite, potassium titanate, aluminum borate, magnesium sulfate, zinc oxide, calcium carbonate, and the like. These fillers may be used alone or in combination of several types. The amount of the filler to be added may be selected as an optimum amount, and up to 50 parts by mass can be added to 100 parts by mass of the semi-aromatic polyamide resin (A). From the viewpoint of the mechanical strength of the resin composition, however, 0.1 to 20 parts by mass is preferred, and 1 to 10 parts by mass is more preferred. In addition, in order to improve the affinity of the fibrous reinforcing material (B) and the filler with the polyamide resin, it is preferred to treat them with an organic agent or a coupling agent, or to use them in combination with a coupling agent during melt compounding. As the coupling agent, any of silane-based coupling agents, titanate-based coupling agents, and aluminum-based coupling agents may be used, and among them, aminosilane coupling agents and epoxysilane coupling agents are particularly preferred.
[0033] The polyamide resin composition of the present invention can contain various additives used in conventional polyamide resin compositions, such as stabilizers, impact modifiers, flame retardants, release agents, sliding properties improvers, colorants, plasticizers, and crystal nucleating agents.
[0034] Examples of the stabilizer include organic antioxidants such as hindered phenol antioxidants, sulfur antioxidants, and phosphorus antioxidants, heat stabilizers, light stabilizers such as hindered amines, benzophenones, and imidazoles, ultraviolet absorbers, metal deactivators, and copper compounds. Examples of the copper compound include copper salts of organic carboxylic acids such as cuprous chloride, cuprous bromide, cuprous iodide, cupric chloride, cupric bromide, cupric iodide, cupric phosphate, cupric pyrophosphate, copper sulfide, copper nitrate, and copper acetate. In addition, it is preferable to contain an alkali metal halide compound as a component other than the copper compound, and examples of the alkali metal halide compound include lithium chloride, lithium bromide, lithium iodide, sodium fluoride, sodium chloride, sodium bromide, sodium iodide, potassium fluoride, potassium chloride, potassium bromide, and potassium iodide. These additives may be used alone or in combination of several types. The amount of stabilizer to be added may be selected optimally, but it is possible to add up to 5 parts by mass per 100 parts by mass of the semi-aromatic polyamide resin (A).
[0035] Examples of the release agent include long-chain fatty acids or their esters or metal salts, amide compounds, polyethylene wax, silicone, and polyethylene oxide. As the long-chain fatty acid, those having 12 or more carbon atoms are particularly preferred, and examples thereof include stearic acid, 12-hydroxystearic acid, behenic acid, and montanic acid, and the carboxylic acid may be partially or entirely esterified with monoglycol or polyglycol, or may form a metal salt. Examples of the amide compounds include ethylene bis-terephthalamide and methylene bis-stearylamide. These release agents may be used alone or as a mixture. The amount of the release agent to be added may be selected from the optimum amount, but it is possible to add up to 5 parts by mass per 100 parts by mass of the semi-aromatic polyamide resin (A).
[0036] The polyamide resin composition of the present invention preferably contains the semi-aromatic polyamide resin (A), the fibrous reinforcing material (B) and the amorphous resin (C) in a total amount of 70 mass% or more, more preferably 80 mass% or more, even more preferably 90 mass% or more, and particularly preferably 95 mass% or more.
[0037] The polyamide resin composition of the present invention can be produced by blending the above-mentioned components by a conventionally known method, for example, by adding each component during the polycondensation reaction of the semi-aromatic polyamide resin (A), by dry blending the semi-aromatic polyamide resin (A) with other components, or by melt-kneading each component using a twin-screw extruder. EXAMPLES
[0038] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. The measured values described in the examples were measured by the following methods.
[0039] (1) Relative Viscosity 0.25 g of the polyamide resin was dissolved in 25 ml of 96% by mass concentrated sulfuric acid, and the viscosity was measured at 20° C. using an Ostwald viscometer.
[0040] (2) Melting point (Tm) and cooling crystallization temperature (Tc2) Using a Toshiba Machine injection molding machine EC-100, the cylinder temperature was set to the melting point of the resin / resin composition + 20 ° C, the mold temperature was set to 140 ° C, and an ISO dumbbell with a length of 170 mm, width of 10.0 mm, and thickness of 4.0 mm was injection molded to prepare a test piece. In order to measure the melting point (Tm) and temperature-reducing crystallization temperature (Tc2) of the obtained test piece, a part of the test piece was weighed out at 5 mg in an aluminum pan and sealed with an aluminum lid to prepare a measurement sample, and then a differential scanning calorimeter (SEIKO INSTRUMENTS SSC / 5200) was used to increase the temperature from room temperature to 350 ° C in a nitrogen atmosphere at 20 ° C / min. At that time, the peak top temperature of the endothermic heat due to melting was taken as the melting point (Tm). In addition, the resin that had been melted once was cooled from 350 ° C at 10 ° C / min, and the exothermic peak temperature due to crystallization was taken as the temperature-reducing crystallization temperature (Tc2).
[0041] (3) Weight average molecular weight 3.1 mg of polyamide resin was weighed out so that the polyamide resin concentration in the sample was about 0.05% by mass. Each sample was dissolved in 4 ml of HFIP / 10 mM sodium trifluoroacetate. The sample solution was filtered through a 0.2 μm membrane filter, and the filtrate was subjected to GPC analysis under the following conditions. The weight average molecular weight was calculated in terms of standard polymethyl methacrylate (PMMA). Equipment: TOSOH HLC-8320GPC Column: TOSOH TSKgel SuperHM-H x 2 + TSKgel SuperH2000 Solvent: HFIP / sodium trifluoroacetate 10mM Flow rate: 0.2ml / min Injection volume: 10μl Temperature: 40℃
[0042] (4) Preparation of test pieces for measuring weld strength / vibration welding conditions From the obtained polyamide resin composition, a vibration welding test piece having a length of 85.0 mm, a width of 10.0 mm, and a thickness of 4.0 mm was produced using an injection molding machine EC-100 manufactured by Toshiba Machine under the conditions of a cylinder temperature of the melting point of the resin + 20° C. and a mold temperature of 140° C. The welded surfaces (10.0 mm × 4.0 mm surfaces) of the obtained test pieces were placed opposite each other, and a vibration welding machine (MICRO-DC) manufactured by Branson was used to obtain a test piece for measuring the weld strength under the following conditions. Frequency: 232Hz Pressure and welding time: 2MPa-6 seconds, 7.5MPa-4 seconds, 18MPa-2 seconds Amplitude: 1.00mm Welding depth: 1.0mm
[0043] (5) Welding strength (tensile breaking strength) In accordance with ISO527-2, the test piece for measuring weld strength was clamped so that the welded part was at the center, and the tensile breaking strength was measured at a tensile test speed of 5 mm / min. This was taken as the weld strength.
[0044] <Semi-aromatic polyamide resin (A)> 8.55 kg of 1.6-hexamethylenediamine, 12.25 kg of terephthalic acid, 8.00 kg of 11-aminoundecanoic acid, 9 g of sodium hypophosphite as a catalyst, hexahydrophthalic anhydride as a terminal regulator, and 16.20 kg of ion-exchanged water were charged into a 50-liter autoclave, pressurized with nitrogen from normal pressure to 0.05 MPa, and then released and returned to normal pressure. This operation was repeated three times to replace with nitrogen, and then the mixture was uniformly dissolved at 135°C and 0.3 MPa under stirring. The solution was then continuously supplied by a liquid delivery pump, heated to 240°C by a heating pipe, and heated for 1 hour. The reaction mixture was then supplied to a pressurized reaction vessel, heated to 290°C, and a portion of the water was distilled off so as to maintain the internal pressure of the vessel at 3 MPa, to obtain a low-order condensate. The low-order condensate was then directly fed to a twin-screw extruder (screw diameter 37 mm, L / D=60) while maintaining the molten state, and polycondensation was carried out in the molten state while removing water from three vents at a resin temperature of 335°C, to obtain semi-aromatic polyamide resin A1. The obtained semi-aromatic polyamide resin A1 was composed of 65.1 mol% of structural units consisting of 1,6-hexamethylenediamine and terephthalic acid and 34.9 mol% of structural units consisting of 11-aminoundecanoic acid, and had a relative viscosity of 2.48, a melting point of 314°C, and a weight-average molecular weight of 29,000. By changing the amount of the end-capping agent, semi-aromatic polyamide resin A2 with a different relative viscosity was obtained. The obtained semi-aromatic polyamide resin A2 was composed of 65.1 mol% of structural units consisting of 1,6-hexamethylenediamine and terephthalic acid and 34.9 mol% of structural units consisting of 11-aminoundecanoic acid, and had a relative viscosity of 2.02, a melting point of 315°C, and a weight average molecular weight of 20,000. The physical properties of the synthesized semi-aromatic polyamide resins A1 and A2 are shown in Table 1.
[0045] [Table 1]
[0046] <Comparative polyamide resin> Polyamide 66 (PA66): Ascend 21-FSR, relative viscosity 2.8, weight average molecular weight 44,000
[0047] <Fiber reinforcement material (B)> Glass fiber: Nippon Electric Glass Co., Ltd., T-275H
[0048] <Amorphous resin (C)> Polyamide 6T6I: Amorphous polyamide resin, EMS "Grivory(R) G21", Tg 125℃ Styrene-N-phenylmaleimide-maleic anhydride copolymer: Denka Co., Ltd., Denka IP MS-CP, Tg 196°C
[0049] Examples 1 to 7, Comparative Examples 1 to 4 Each raw material was weighed out according to the compounding ratio shown in Table 2 (other additives had the following contents relative to the composition), and extruded in a 26φ twin-screw extruder (TEM26SS manufactured by Toshiba Machine Co., Ltd.) with the cylinder temperature set to 330°C for the semi-aromatic polyamide resin (A) and 290°C for the comparative polyamide resin, at a screw rotation speed of 150 rpm. A mixture of predetermined amounts of components (A) and (C) was fed from a hopper, and component (B) was fed by side feed and melt-kneaded to obtain a polyamide resin composition as a molding material. Per 100 parts by mass of the total polyamide resin, 0.5 parts by mass of calcium montanate (Clariant Chemicals, CS-8CP) was used as a release agent, and 0.3 parts by mass of Adeka STAB AO-80 (ADEKA Corporation) was used as a stabilizer. The obtained polyamide resin composition was used to evaluate various properties, and the evaluation results are shown in Table 2.
[0050] [Table 2]
[0051] As is clear from the results in Table 2, by adding the amorphous resin (C), the welding strength is high, and even when a high pressure is applied during welding, the welding strength does not decrease. In other words, the welding time can be shortened, and productivity is increased. It can also be confirmed that the higher the weight average molecular weight of the semi-aromatic polyamide resin (A), the higher the welding strength. [Industrial Applicability]
[0052] INDUSTRIAL APPLICABILITY The polyamide resin composition of the present invention is suitable for engine cooling water system parts which require a welding process, and can be used for radiator tank parts, coolant reserve tanks, water pipes, water inlet pipes, water outlet pipes, water pump housings, water pump impellers, water valves, coolant sub-tanks, and the like.
Claims
1. The composition contains 0 to 150 parts by mass of a fibrous reinforcing material (B) and 5 to 50 parts by mass of a non-crystalline resin (C) relative to 100 parts by mass of a semi-aromatic polyamide resin (A), The polyamide resin composition for welding is characterized in that the semi-aromatic polyamide resin (A) is a copolymer polyamide resin having as its constituent components (a) 50 to 80 mol % of hexamethylene terephthalamide units and (b) 50 to 20 mol % of undecane amide units.
2. 2. The polyamide resin composition for welding according to claim 1, wherein the weight average molecular weight of the semi-aromatic polyamide resin (A) is 15,000 to 60,000.
3. 3. The polyamide resin composition for welding according to claim 1, wherein the non-crystalline resin (C) is a non-crystalline polyamide resin.
4. A molded part having a welded portion made of the polyamide resin composition according to any one of claims 1 to 3.
5. 4. An engine cooling water system part comprising the polyamide resin composition according to claim 1.
Citation Information
Patent Citations
Manufacture of part for engine cooling water system
JP1998264254A
Polyamide resin composition for part of engine cooling water system, and part of engine cooling water system using the same
JP2012153798A
Filament composition for producing fused filaments and method of use thereof
JP2019534393A
Metal / resin composite structure and method for manufacturing metal / resin composite structure
WO2019082983A1
Polyamide resin composition, molded body thereof, and method for manufacturing laser-welded body
WO2019160117A1